Pathways for horizontal gene transfer in bacteria revealed by a global map of their plasmids - Santiago Redondo-Salvo (Nature Portfolio, 2020)
Plasmids can mediate gene transfer across bacterial populations. Here, the authors describe a global map of the prokaryotic plasmidome, where plasmids organize into discrete ‘plasmid taxonomic units’ based on their genomic composition and pairwise sequence identity.